Establishment of Forensic Land Surveying in the System of Forensic Science Organizations of the Russian Ministry of Justice - Zlata V. Trifonova (Теория и практика судебной экспертизы, 2018)
The ever-increasing need for land survey expertise in judicial proceedings, as well as the complexity of this branch of forensic practice require a special approach to the interpretation of theoretical foundations of forensic land surveying, which led to the author's attempt to define its basic theoretical concepts. The article also considers and describes the most common tasks performed by forensic land survey practitioners in land dispute cases.